2003
DOI: 10.1093/ajcn/77.1.226
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing lactating women with flaxseed oil does not increase docosahexaenoic acid in their milk

Abstract: Dietary flaxseed oil increased the breast-milk, plasma, and erythrocyte contents of the n-3 fatty acids ALA, EPA, and DPA but had no effect on breast-milk, plasma, or erythrocyte DHA contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
81
0
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 31 publications
13
81
0
5
Order By: Relevance
“…Our finding of a significant increase in ALA levels after a dietary supplement of flaxseed is similar to previous reports (Francois et al, 2003;Austria et al, 2008;Harper et al, 2006a, b). For example, Francois et al (2003) showed that plasma ALA values increased after 2 and 4 weeks of 20 g flaxseed oil supplementation in lactating women aged 28-39 years. Cunnane et al (1995) found increased plasma ALA in healthy young adults with a mean age of 25 ± 3 years after 2 weeks of supplementation with 50 g of milled flaxseed per day.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of a significant increase in ALA levels after a dietary supplement of flaxseed is similar to previous reports (Francois et al, 2003;Austria et al, 2008;Harper et al, 2006a, b). For example, Francois et al (2003) showed that plasma ALA values increased after 2 and 4 weeks of 20 g flaxseed oil supplementation in lactating women aged 28-39 years. Cunnane et al (1995) found increased plasma ALA in healthy young adults with a mean age of 25 ± 3 years after 2 weeks of supplementation with 50 g of milled flaxseed per day.…”
Section: Discussionsupporting
confidence: 93%
“…Again, the effects in the ground flaxseedsupplemented groups did not achieve statistical significance although similar trends were observed in both age groups. The lack of change in plasma DHA is in agreement with several previous investigations (Francois et al, 2003;Wallace et al, 2003;Austria et al, 2008;Harper et al, 2006a, b). Interconversion of the n-3 fatty acids appears to be limited in humans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The levels of 22:6n-3 in captive-living anthropoid populations were significantly higher than those of their wild-living superfamily counterparts. Data from humans (Brenna, 2005;Francois et al, 2003) and baboons (Greiner et al, 1997;Su et al, 2005) also support the hypothesis that 22:6n-3 levels in milk increase with an increased source of preformed 22:6n-3.…”
Section: Discussionmentioning
confidence: 82%
“…The concentration of these LCPUFA in milk depends on dietary supply (primarily animal products, such as fish and eggs) and the desaturation and elongation of their n-3 and n-6 PUFA precursors. Data from humans [Brenna, 2002;Francois et al, 2003] and baboons [Greiner et al, 1997;Su et al, 2001] indicate that 22:6n-3 levels in milk increase more with an increased source of preformed 22:6n-3 rather than increases in 18:3n-3. It is difficult to draw conclusions as to the source of milk 22:6n-3 without a better understanding of LCPUFA concentration of the diet and efficiency of the species in conversion to LCPUFA.…”
Section: Discussionmentioning
confidence: 99%